2015
DOI: 10.1111/cei.12594
|View full text |Cite
|
Sign up to set email alerts
|

Galectin isolated from parasite inhibits remission of experimental autoimmune encephalomyelitis by up-regulating autoantibody

Abstract: SummaryRecently, parasite infections or parasite-derived products have been suggested as a therapeutic strategy with suppression of immunopathology, which involves the induction of regulatory T cells or/and T helper type 2 (Th2) responses. In a recent study, researchers reported that constructed recombinant galectin (rTl-gal) isolated from an adult worm of the gastrointestinal nematode parasite Toxascaris leonina attenuated clinical symptoms of inflammatory bowel disease in mice treated with dextran sulphate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Administration of Tl-gal to EAE mice increased the number of CD45R/B2201 B cells and production of autoantibody [anti-myelin oligodendrocyte glycoprotein (MOG)35–55] in serum at the chronic stage with changes in cytokine TNF-α and IFN-γ in spleen cells. Unexpectedly, despite the similarly of parasitic Tl-gal to human Gal-9, the proteins exhibit dissimilar influences on EAE course, which can indicate different functions of nematode and host galectin ( Bing et al., 2015 ) or possibly their competitive effects.…”
Section: Parasitic Cns Infectionsmentioning
confidence: 99%
“…Administration of Tl-gal to EAE mice increased the number of CD45R/B2201 B cells and production of autoantibody [anti-myelin oligodendrocyte glycoprotein (MOG)35–55] in serum at the chronic stage with changes in cytokine TNF-α and IFN-γ in spleen cells. Unexpectedly, despite the similarly of parasitic Tl-gal to human Gal-9, the proteins exhibit dissimilar influences on EAE course, which can indicate different functions of nematode and host galectin ( Bing et al., 2015 ) or possibly their competitive effects.…”
Section: Parasitic Cns Infectionsmentioning
confidence: 99%
“…This includes dosage and timing of inoculation with larvae, ova, or excreted-secreted (E/S) products from 12 different helminthic species, and adoptive transfer of leukocytes treated with E/S products or isolated from helminth-infected animals into mice or rats prior to or after EAE immunization (Figure 1, Table 1). 1335…”
Section: Helminths Influence Disease Development In Rodent Models Of Msmentioning
confidence: 99%
“…36 Only one study reported detrimental effects of HIT: treatment of Toxascaris leonina -derived galectin following EAE immunization prevented remission of EAE-induced paralytic symptoms. 34…”
Section: Helminths Influence Disease Development In Rodent Models Of Msmentioning
confidence: 99%
“…The clinical symptoms of DSS-treated mice after pre-treatment with rTl-gal were less profound than those of untreated group (Kim et al, 2010). However, in an experimental autoimmune encephalomyelitis model, rTl-gal exhibited a function distinct from that of Gal-9 and aggravated disease severity by enhancing the production of pathogenic autoantibody and proinflammatory cytokines (Th2 response) (Bing et al, 2015).…”
Section: Parasite Galectins and Their Roles In Host-parasite Intermentioning
confidence: 99%